Les genres littéraires participent de domaines: en relisant Croce, Frye et McLuhan - Jean Bessière (Interlitteraria)
Literary Genres Are Parts of Fields: Reading Croce, Frye and McLuhan. Literary critics widely apply the notion of genre to literary works; the use of the notion of field is far less frequent. This application of the notion of genre is defined as a tool to code literary works and to subsume the many variants of coding under specific names – the names of genres. The notion of literary genre and its realities are relativistic; they do not succeed in accounting for literary works’ singularities and similarities. Any systematic use of literary genres in criticism ends with inconsistent views of what is supposed to be the whole of literary genres. Genette’s notion of ‘architext’ illustrates this impasse. The notion of field – here translated in French by ‘domain’ and specified by the expression ‘domaine de sens’ (field of sense) – enables critics and readers to align views on singularities and similarities, to reject any systematic perspective and to outline literary works’ differences, proximities and conti nuities. The notion of ‘domaine de sens’ deprives references to constant kinds of forms/ genres of theoretical and practical usefulness. Literary works are constant because they are texts. As texts, they require no coding to be identified as literary. They just ‘appear’ to be works when they are linked to fields of sense, i.e. linked to the discourses and semantics of the place and time of their writing or reading. These discourses and semantics may include literary genres. Fields of sense are innumerous and change according to the place and time of works’ writing and reception, and each field of sense eventually comprises many works. Fields of sense explain literary works’ proximities and chains across time. Croce’s, Frye’s and McLuhan’s theses about literary genres support the aforementioned argument.